EVALUATION OF NUTRITIONAL CHANGES IN BROCCOLI AFTER DIFFERENT TIMES AND COOKING METHODS (REMUNOM, 2023)
Micronutrients, mineral salts and vitamins are available in tiny fractions in various types of food and are essential for the maintenance and nutrition of human beings. Because it cannot synthesize sufficient amounts for the nutritional demand, the human body meets its needs for mineral salts and vitamins through the consumption of external sources. Nutritious food prevents chronic disease as long as it is consumed daily. They can be eaten raw or thermally processed. The thermal process used for cooking alters the nutritional content of foods. The objective of the study was to investigate changes in the amounts of zinc (Zn), iron (Fe) and vitamin C in broccoli after different cooking treatments. The methodology proposed by Fraige, Crespilho and Rezende was used to determine zinc (Zn). Iron (Fe) was evaluated using the methodological procedure proposed by Freitas. Vitamin C was determined through titrimetric analysis of iodometric oxide reduction according to the methodology stipulated by Instituto Adolfo Lutz. There were significant differences in retention of nutrients evaluated in broccoli. The cooking methods using water steam and microwaves did not show significant differences between them, with steam cooking being the most efficient process in preserving the analyzed micronutrients. Vitamin C showed a significant difference between the in natura state and cooking, generating a 26.05% reduction in vitamin C. The amount of iron did not show a significant difference between cooking treatments used. Zinc showed a significant difference between the cooking treatments and the in natura sample. The use of steam prevents losses due to leaching of nutrients that may occur during the stages of cleaning and cooking food. Losses of amounts of zinc, iron and vitamin C were reduced with processing using steam, this method being the most suitable for preserving nutrients.